PENGUKURAN KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA MENGGUNAKAN METODE ANALISIS FAKTOR DI KOPSYAH BMI KECAMATAN TELUKNAGA - Siti Juhaeriyah; Yulianti Rusdiana; Tabah Heri Setiawan (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
BMI Islamic cooperative Teluknaga Branch is the third branch established and experienced a sharp decline in the number of members in 2019. Members are one part of the cooperative's identity (From, By and For Members), and have a very strong influence on other performance. This study aims to analyze the factors that affect the satisfaction of Kopsyah BMI members in Teluknaga District. The sample studied was 400 respondents from 6,705 total population of members of Kopsyah BMI Teluknaga Branch. The variables used are 23 variables using factor analysis. The results showed that 23 variables can be reduced to 5 factors. There are five factors formed from the reduction process, namely, the first factor is Responsiveness (F2) with the most dominant correlation value of 0.974, the second factor is Tangible (F5) has a correlation value of 0.787, the third factor is Reliability (F1) with a correlation value of 0.627, Fourth, Empathy (F4) with a correlation value of 0.547, and the fifth factor Assurance (F3) with the smallest correlation value of 0.087, are things that must be considered and used as further evaluation to attract people to become members of the Kopysah BMI in Teluknaga District